Reduction of Hepatic Fat Content by Dulaglutide for the Treatment of Diabetes Mellitus: A Two‐Centre Open, Single‐Arm Trial - Chuanfeng Liu; Yu Xin; Yajing Huang; Lili Xu; Ruizhi Zhou; Yangang Wang; Wei Wang (Endocrinology, Diabetes & Metabolism, 2025)
ABSTRACT Background With the elevated level of NAFLD prevalence, the incidence of diabetes, hypertension, metabolic syndrome and other diseases is also significantly elevated. GLP‐1RA can exert weight loss, glucose‐lowering effects and various nonglycaemic effects. However, the relationship between quantitative reduction in hepatic fat content and improvement of pancreatic islet function by GLP‐1RA is unclear. Methods This trial was a single‐arm open cohort study. A total of 38 patients with T2DM and NAFLD were enrolled in the GLP‐1RA treatment group. The included patients were tested for biochemical and blood glucose levels, adiponectin and FGF21 levels, and liver fat content was measured using MRI. Measure the above indicators again after at least 3 months of GLP‐1RA treatment. Divided into Q1 (average decrease of 0.37%) and Q2 (average decrease of 8.6%) groups based on the degree of reduction in liver fat content. Results Q2 group showed an average reduction in liver fat content of 8.6%, a decrease in glycated haemoglobin of 18.17%, a weight loss of 7.29% and an increase in fasting c‐peptide release by 1.03%, 1‐h and 2‐h postprandial c‐peptide release by 28.86% and 18.28% respectively. In contrast, Q1 group had an average reduction in liver fat content of 0.37%, a decrease in glycated haemoglobin of only 6.53%, a weight loss of 3.41%, a decrease in fasting c‐peptide release by 1.91% and an increase in 1‐h and 2‐h postprandial c‐peptide release by 19.18% and 11.66% respectively. Conclusion Reduction in liver fat content effectively improves pancreatic islet function secretion, particularly postprandial c‐peptide secretion, especially in the first hour after a meal. This improvement leads to a decrease in glycated haemoglobin levels and promotes better compliance with blood glucose control.